1984
DOI: 10.1007/bf00291559
|View full text |Cite
|
Sign up to set email alerts
|

Steroid sulphatase in man: A non inactivated X-locus with partial gene dosage compensation

Abstract: Steroid sulphatase (STS) activity was measured with two different steroid substrates in leucocytes from normal human males and females, from females heterozygous for STS deficiency and recessive X-linked ichthyosis, and from individuals with numerical X chromosome aberrations. The results indicate non-inactivation with a partial gene dosage compensation at the STS locus. It is estimated that STS loci on inactive X chromosomes express approximately 45% of the STS activity originating from STS loci on active X c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…The characterization of the enzyme showed the same pattern as that reported for human chorion and decidual tissue [11]. The difference between males and females in steroid sulfatase enzyme activities has been demonstrated in various human tissues such as the placenta [12], lymphocytes [3, [12][13][14][15] 13,15] indicating that the measurement of leukocyte steroid sulfatase makes possible rapid differentiation of patients with RXLI from those with other types of ichthyosis. They also suggested that this method makes possible the identification of RXLI carriers diagnosed from the clinical appearance and pedigree analysis.…”
supporting
confidence: 58%
“…The characterization of the enzyme showed the same pattern as that reported for human chorion and decidual tissue [11]. The difference between males and females in steroid sulfatase enzyme activities has been demonstrated in various human tissues such as the placenta [12], lymphocytes [3, [12][13][14][15] 13,15] indicating that the measurement of leukocyte steroid sulfatase makes possible rapid differentiation of patients with RXLI from those with other types of ichthyosis. They also suggested that this method makes possible the identification of RXLI carriers diagnosed from the clinical appearance and pedigree analysis.…”
supporting
confidence: 58%
“…1979). However, the reported dosage effects have been less than 2 to 1 (Ropers et al, 1981: Lykkesfeldt et al, 1984. These results suggest that partial dosage compensa tion may occur for the human STS gene on the inactive X (Lyk kesfeldt et al, 1984).…”
Section: Resultsmentioning
confidence: 91%
“…Although the segments Xq22, 24, 26, 28 are not involved in these early replicators, some summation effect in multiple X individuals may be possible. On the other hand, according to Lykkesfeldt et al (1984) even in the case of steroid sulfatase (STS) loci on inactive X chromosome (assigned to Xp22), it is estimated that it expresses only 45~ of the active X chromosome. They indicated that the STS activities in a 47,XXX individual and in a 49,XXXXY individual were in the female range, which also supports the conclusion of a reduced expression of STS loci in heterocyclic inactive X chromosomes.…”
Section: Discussionmentioning
confidence: 99%